The HEPS project - Jiao, Yi; Xu, Gang; Cui, Xiao-Hao; Duan, Zhe; Guo, Yuan-Yuan; He, Ping; Ji, Da-Heng; Li, Jing-Yi; Li, Xiao-Yu; Meng, Cai; Peng, Yue-Mei; Tian, Sai-Ke; et al. (Journal of synchrotron radiation, 2018)
The High Energy Photon Source (HEPS), a 6 GeV green‐field diffraction‐limited storage ring light source, will be built in Beijing, China. The HEPS design has been evolving for about ten years, and is now mostly finished and ready for construction. The storage ring is based on a modified hybrid seven‐bend achromat (7BA) design, where bending magnets with reverse bending angles and longitudinal gradients are adopted to reach an ultralow natural emittance of 34.2 pm with a circumference of 1360.4 m. The central slice of the dipole in the middle of the modified hybrid 7BA, with flexible magnetic field, is used as the source of the bending‐magnet beamline. Moreover, alternating high‐ and low‐beta sections are specially designed to generate and deliver X‐ray synchrotron radiation with high brightness of 5 × 1022 photons s−1 mm−2 mrad−2 (0.1% bandwidth)−1. Here, the HEPS storage ring design and solutions to the challenges inherent in this ultralow‐emittance design are presented. Details of the High Energy Photon Source (HEPS), a 6 GeV green‐field diffraction‐limited storage ring light source to be built in China, are presented.